Lecture #4 Notes

# Lecture #4 Notes - Matrix Theory Math6304 Lecture Notes...

This preview shows pages 1–3. Sign up to view the full content.

Matrix Theory, Math6304 Lecture Notes from September 6, 2012 taken by Nathaniel Hammen Last Time (9/4/12) Diagonalization: conditions for diagonalization Eigenvalue Multiplicity: algebraic and geometric multiplicity 1 Further Review 1.1 Warm-up questions 1.1.1 Question. If A M n has only one eigenvalue λ (of multiplicity n ) and is diagonalizable, what is A ? Answer. Because A is diagonalizable, there exists an invertible S M n such that S 1 AS is diagonal. In fact, because all eigenvalues are λ , we have A = S ( S 1 AS ) S 1 = S λ IS 1 = λ SS 1 = λ I 1.1.2 Question. Let A M n and f ( t ) = det ( I + tA ) . What is f ( t ) in terms of A ? Answer. The i, j th entry of ( I + tA ) is δ i,j + ta i,j , so f ( t ) = det ( I + tA ) = σ S n sgn ( σ ) n j =1 ( δ σ ( j ) ,j + ta σ ( j ) ,j ) = σ S n sgn ( σ ) n j =1 δ σ ( j ) ,j + t n j =1 a σ ( j ) ,j i = j δ σ ( i ) ,i + o ( t 2 ) where S n is the set of permutations of n elements and sgn ( σ ) is +1 if σ is an even permutation and -1 if σ is an odd permutation. Di ff erentiating f ( t ) gives f ( t ) = σ S n sgn ( σ ) n j =1 a σ ( j ) ,j i = j δ σ ( i ) ,i + o ( t ) = n j =1 a j,j + o ( t ) = tr ( A ) + o ( t ) 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This last equality holds because i = j δ σ ( i ) ,i is only nonzero when σ ( i ) = i for all i = j , which only occurs when σ is the identity. When we plug 0 into the equation, we get that f (0) = tr ( A ) . 1.4 Similarity (cont’d) 1.4.27 Theorem. A matrix A M n is diagonalizable if and only if the geometric and algebraic multiplicities of each eigenvalue are equal. Proof. We begin by noting that if λ j and λ k are eigenvalues of A with λ j = λ k , then their eigenspaces intersect trivially; that is E λ j E λ k = { 0 } . To show this, let x E λ j E λ k . Then λ j x = Ax = λ k x , which implies x = 0 because λ j = λ k . Thus if { v 1 , v 2 , . . . , v m j } is a basis for E λ j and { u 1 , u 2 , . . . , u m k } is a basis for E λ k , then { v 1 , v 2 , . . . , v m j } { u 1 , u 2 , . . . , u m k } is a linearly independent set, and forms a basis for E λ j + E λ k . Inductively iterating this, we obtain a basis for E λ 1 + · · · + E λ r
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern